(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
in this article highlighted the different methods of teaching English. The aim of this paper is to show the use of innovative techniques for teaching English communication skill to learners. Novel methods such audio video aids, games, group discussions, role play, brain storm will provide an easy way for learning the English communication skill and increase the confidence of the learners